The Impact of Natural Lighting on Fostering Sustainable Behavior in Educational Buildings - Mosul University Buildings of as a case study - Al-qemaqchi, Nahedh Taha; Rashan, Madyan Maher (Sulaimani Journal for Engineering Sciences, 2017)
There were an increased importance and vitality of the subject of sustainability in now days; after the modern era has witnessed a rapid depletion of natural resources. It has been considered that the natural lighting was one of the main topics targeted in order to create a sustainable built environment. This research tries to draw the effect of natural lighting on the behavioral activities and their relationship with the built environment, through its impact on dynamic area termed "personal space", which plays a major role in regulating individual behavior, and interactions with the rest of the individuals in the built environment. The study assumes that the high intensity of natural lighting supports sustainable behavior among individuals. It also tests that hypothesis into the lecture halls at universities to highlight its validity and to use the results as design indicators for such spaces.
Keywords: Sustainability; Personal Space; Natural Lighting; Sustainable Behavior